Analysis of the Income of Rina Bolo-Bolo Innovative Banana Commodity Culinary Business - Arina Putri Sabrita A. T; Andi Herman Jaya; Yohan; Ika Rafika; Muhammad Ichsan (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This research aims to o analyze the income level and business viability of the “Rina Bolo-Bolo” culinary business in Palu City. The method used is a descriptive approach employing both qualitative and quantitative data collection techniques, including direct observation and documentation of production costs and monthly sales revenue. The results of the study show that the total production costs incurred per month amount to Rp2,925,458, with total revenue reaching Rp6,000,000, resulting in a net income of Rp3,073,542. An R/C Ratio of 2.05 indicates that every rupiah spent generates revenue of Rp2.05, indicating that Rina Bolo’s business is highly viable. Based on these findings, it can be concluded that Rina Bolo-Bolo’s business has very promising prospects and is worthy of development as a highly profitable sustainable micro-enterprise model.